Resistance Test of Themba Oil Palm Variety against Several Leaf Spot Pathogens - Budi, Ismed Setya; Mariana, Mariana; Fitriyanti, Dewi; Tuti, Harlina Kusuma; Mariah, Yanti; Suyanti, Aprilia Putri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Leaf spot disease is a major constraint during the oil palm nursery stage, reducing seedling quality and affecting long-term productivity. This study evaluated the resistance of the Themba oil palm variety against three leaf spot pathogens: Curvularia spp., Fusarium spp., and Nigrospora spp., based on incubation period, disease intensity, and plant resistance. The research was conducted from June to November 2025 at the Phytopathology Laboratory and greenhouse of the Plant Protection Study Program, Faculty of Agriculture, Lambung Mangkurat University. Pathogens were inoculated on seedlings selected purposively for uniform age and condition, with four replicates per treatment. The incubation period was monitored daily, and disease intensity was scored periodically. Data were analyzed descriptively using mean values to compare plant responses. Results showed all pathogens caused leaf spot symptoms, but with different progression rates. Curvularia spp. was the most aggressive, while Nigrospora spp. developed more slowly with lower severity. Overall, Themba seedlings exhibited moderate resistance to the tested pathogens, indicating their potential in managing leaf spot disease during the nursery stage, especially when supported by optimal environmental management. These findings provide valuable insights for selecting resistant varieties and implementing integrated disease management strategies in oil palm cultivation.